BLOCKCHAIN ​​VOTING TECHNOLOGY FOR AN ELECTORAL SYSTEM - Quinto Martínez, José; Pilay Salvatierra, Luis; Echeverria Desiderio, Segundo (EASI: Engineering and Applied Sciences in Industry, 2022)
Electoral processes in the world must be characterized by the freedom to elect their leaders, but also by the integrity of the election carried out by citizens, to avoid fraud; however, in many countries manual voting is still accomplished, without considering the advantages and benefits of technology. In this research, the objective was to analyze Blockchain technology as a potential tool for the development of a new form of voting. Additionally, a mechanism for applying this technology is proposed and with a goal to meet the expectations of the voters and the organizing entities of the voting, with the purpose of providing safe citizen participation which facilitates processes and reduces costs, thanks to the implementation of Blockchain technology. This system will help the transparency of the process, taking care of privacy and its validity. The results cannot be falsified, and the counting speed would be increased. Voters will be able to access their citizen participation through a unique code, ensuring that their vote is registered and immutable.
Keywords: blockchain technology; voting system; electoral processes; votes; cryptography